Swift isotropic heat transport of 3D graphene platform-based metal-graphene composites. (15th October 2021) - Ryu, Hyesu; Rho, Hokyun; Lee, Seog Woo; Lee, Seoung-Ki; Lee, Hyunjung; Bae, Sukang; Kim, Tae-Wook; Cho, Meoung Whan; Ha, Jun-Seok; Lee, Sang Hyun
Abstract: Despite the remarkable thermal properties of graphene, the heat transport along the z-axis is intrinsically limited by the van der Waals interactions, leading to thermal anisotropy in multilayered graphene (or graphite) and its composites. Herein, we report a graphene foam (GF) with three-dimensional (3D) pore structure-based metal composites with excellent isotropic thermal conductivity and fast heat transfer performance. The 3D periodic structure of the GF–copper composites composed of high-quality multilayer graphene and copper was formed via a chemical vapor deposition (CVD) and a spark plasma sintering (SPS) process. The high-quality graphene layers in GF were well-bonded to copper, forming a clear interface without voids in the consolidated composites. Owing to the uniform 3D interconnection of graphene layer in the GF, in spite of less than 1 vol% carbon in the copper matrix, the GF–copper composites showed high isotropic thermal conductivity, which was higher by about 11 and 6% for in-plane and through-plane, respectively, than those of the bulk copper (∼400 W m −1  K −1 ). The superior performance of the 3D graphene-based metal–carbon composites offers remarkable opportunities in thermal management for advanced electronic and optoelectronic devices requiring high power density and efficiency. Graphical abstract: Image 1